2020
DOI: 10.1155/2020/4160898
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance Evolution Behavior of Loess Soil under Triaxial Compression

Abstract: This paper presents an investigation into the evolution law of the structural effects of Xi’an loess soil, based on the disturbed state concept. First, a series of consolidated and drained triaxial compression tests were performed on undisturbed and remoulded loess samples prepared at five different moisture contents and tested at four different confining pressures. Second, two disturbance functions with different parameters were proposed to quantify mathematically the structural effects of loess. Finally, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In recent years, with the deepening of mathematical and mechanical theories and the rapid development of computer technology, numerical simulation methods have been widely used in the theoretical research and engineering problem processing of geotechnical engineering [70][71][72][73][74][75][76][77] FEM is the widely used simulation method in the study of rock fracture mechanics [78,79]. The solution of the stress field at the crack tip, the calculation of the stress intensity factor, and the J-integral can all be solved by FEM.…”
Section: Numerical Simulation Methodsmentioning
confidence: 99%
“…In recent years, with the deepening of mathematical and mechanical theories and the rapid development of computer technology, numerical simulation methods have been widely used in the theoretical research and engineering problem processing of geotechnical engineering [70][71][72][73][74][75][76][77] FEM is the widely used simulation method in the study of rock fracture mechanics [78,79]. The solution of the stress field at the crack tip, the calculation of the stress intensity factor, and the J-integral can all be solved by FEM.…”
Section: Numerical Simulation Methodsmentioning
confidence: 99%
“…Sample preparation is one of the critical steps during the performance of a laboratory-scale hydraulic fracturing experiment. To prepare a sample, first, the material, geometry, and dimension need to be determined, followed by processing such as cutting, mixing, curing, drilling, and casing [88][89][90][91][92]. When selecting a sample material, the in situ reservoir formations are the preferences.…”
Section: Sample Preparationmentioning
confidence: 99%
“…From 1966 to 1978, researchers found that the newly accumulated loess has similar characteristic indexes to Q3 loess, but it has high compressibility and low bearing capacity (Shaanxi Comprehensive Survey Institute, 1973). Since 1978, a breakthrough has been made in the microstructure, pore structure, and its influence on the engineering properties of loess Wang and Lin, 1990;Xu and Guo, 2020;Xu et al, 2020). Unfortunately, none of these methods take into account the dynamic stress like earthquake.…”
Section: Introductionmentioning
confidence: 99%